The Development of Independent Character Values in Dahlia Kindergarten, Telaga District - Rahmatia A. Moonggalo, Tuti; Febriyanti Suleman, Vera; Moha, Rahmilta; Wahyuni, Eka (PT Literasi Nusantara Publisher, 2022)
Kindergarten is an education for early childhood that is on the formal path, Early Childhood education not only forms children who are smart but personable and have character. There are 18 values of character education to be implanted in early childhood. To gauge whether early childhood already has the character applied by the school within a certain period of time, an assessment is required. Assessment of character education is intended to detect the character formed in early childhood during the study in kindergarten.